2005
DOI: 10.1038/sj.ijir.3901410
|View full text |Cite
|
Sign up to set email alerts
|

Inventories for male and female sexual dysfunctions

Abstract: Several illnesses can distress sexual health and disrupt sexuality, an integral part of being human. These illnesses are not different in origin from those affecting other health areas, but, because sexuality is involved, effective communication and empathy between the physician and the patient may be severely hindered by negative feelings such as anxiety and guiltiness. A detailed general and sexual history is, however, an essential step in evaluating patients for sexual dysfunction (SD). Finding the correct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
106
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(109 citation statements)
references
References 71 publications
0
106
0
3
Order By: Relevance
“…58 This clinical tool has the advantage of being standardized, easy to administer and score, and provides normal values in general and pathological populations. 59 Previous evidence linking FSD to obesity is very scanty. In 171 postmenopausal women, Kirchengast et al 56 reported that body weight and BMI were significantly related to the degree of reduced sexual interest.…”
Section: Obesity Metabolic Syndrome and Female Sexual Functionmentioning
confidence: 99%
“…58 This clinical tool has the advantage of being standardized, easy to administer and score, and provides normal values in general and pathological populations. 59 Previous evidence linking FSD to obesity is very scanty. In 171 postmenopausal women, Kirchengast et al 56 reported that body weight and BMI were significantly related to the degree of reduced sexual interest.…”
Section: Obesity Metabolic Syndrome and Female Sexual Functionmentioning
confidence: 99%
“…9 This clinical tool has the advantage of being standardized, easy to administer and score and provides normal values in general and pathological populations. 10 To the best of our knowledge there are no reported studies assessing the relation between FSFI and body weight in women. Therefore, the aims of this study were: (a) to identify women with pathological values of FSFI across a wide range of body weight; (b) to compare them with control, age-matched women with normal values of sexual function and (c) to investigate the relationship between the amount and distribution of body fat and sexual function.…”
Section: Introductionmentioning
confidence: 99%
“…A further advantage of the structured interview over the self-reported questionnaire is that a face-to-face interview facilitates a virtuous, intimate physician-patient relationship. 32 In fact, structured interviews have been found to have a greater diagnostic value than self-reported questionnaires in other contexts when involving possibly sensitive issues. 33 We have recently developed a brief (12 items) structured interview (ANDROTEST) specifically designed for the screening of hypogonadism (total T ,10.4 nmol l…”
Section: Structured Inventories For Detecting Lohmentioning
confidence: 99%